On the English edition of Van Rheede’s Hortus Malabaricus by K. S. Manilal (2003) - H. Y. Mohan Ram (CURRENT SCIENCE, 2005)
Van Rheede, the Dutch Governor of Cochin, a soldier who had no training in botany, became fasci- nated by the flora of Malabar, compiled and published a unique 12-volume work Hortus Malabari- cus between 1678 and 1693. K. S. Manilal has spent over 35 years rendering Hortus Malabaricus to English. Through this stupendous task, he has opened a vast treasure-house to scientists, medical practioners, linguists and historians.